Incidence of hepatocellular carcinoma in patients with non-alcoholic fatty liver disease: A meta-analysis and meta-regression. (28th May 2021) - Orci, L; Caballol, B; Sanduzzi-Zamparelli, M; Sapena, V; Colucci, N; Torres, F; Bruix, J; Reig, M; Toso, C
Abstract: Objective: Nonalcoholic fatty liver disease (NAFLD) may be a risk factor for hepatocellular carcinoma (HCC), but the extent of this association still needs to be addressed. Pooled-incidence rates of HCC across the disease spectrum of NAFLD have never been estimated by meta-analysis. Methods: In this systematic review, we searched Web of Science, Embase, Pubmed, and the Cochrane library from January 1st, 1950 through July 30th, 2020. We included studies reporting on HCC incidence in patients with NAFLD. The main outcomes were pooled HCC incidences in patients with NAFLD at distinct severity stages. Summary estimates were calculated with random-effects models. Sensitivity analyses and meta-regression analyses were carried out to address heterogeneity. The protocol for this review was registered in Prospero (CRD42018092861). Results: Eighteen studies, with a total of 470, 404 patients were included. In patients with NAFLD at a stage earlier than liver cirrhosis, HCC incidence was of 0.03 per 100 person-years (PYs) (95% confidence interval 0.01-0.07, I2=98%). This rate rose to 3.78 per 100PYs (2.47-5.78, I2=93%) when considering studies that only included patients with liver cirrhosis. Among the latter patients, those undergoing regular HCC screening displayed an incidence of 4.62 per 100PYs (2.77-7.72, I2= 77%). Conclusion: Patients with NAFLD-related liver cirrhosis have a risk of developing HCC similar to that reported for patients with cirrhosis from other etiologies. Evidence documenting the risk in patients with NASH or simple steatosis is limited, but HCC incidence in these populations may lie below thresholds used to recommend HCC screening. Well-designed prospective studies in these subsets of patients are needed.